Peran Guru Kristen Menghadirkan Shalom Community Melalui Prinsip Kedisiplinan [The Role of Christian Teachers in Providing the Shalomic Community Through Disipline] - Yemima Christiani; Kurniawati Martha (Universitas Pelita Harapan, 2021)
Learning discipline is needed to create effective and conducive learning conditions to achieve learning objectives. The problem of student discipline is a topic that teachers encounter quite often, especially during the current online learning period. Violation of classroom rules in online learning makes teachers confused about what kind of consequences will be given to students. This disciplinary violation needs to be followed up by the teacher. The sinful nature in the student causes him to deviate from God's truth, and Christian teachers have the responsibility of bringing students back to God's truth. However, the disciplinary action that the teacher gives must be in accordance with the principles of discipline according to God's Word and bring shalom in the classroom community. As a solution, the teacher takes a communication and relational approach that includes six methods for disciplining PAUD students. This approach is based on a disciplinary principle that refers a biblical Christian viewpoint. The teacher acts as a servant and shepherd, that is, the teacher becomes a living example who guides students to return to God's truth. The purpose of this paper is to describe the role of Christian teachers in presenting the Shalom Community in the classroom through disciplinary principles based on literature studies based on a biblical Christian view.